2017
DOI: 10.1016/j.jsxm.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and Experiences with Surgical Interventions for Female Genital Mutilation/Cutting (FGM/C): A Systematic Review

Abstract: There are some data on women's motivations for surgery for FGM/C-related concerns, but little is known about whether women are satisfied with the surgery, and experiences appear mixed. Berg RC, Taraldsen S, Said MA, et al. Reasons for and Experiences With Surgical Interventions for Female Genital Mutilation/Cutting (FGM/C): A Systematic Review. J Sex Med 2017;14:977-990.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…Furthermore, although there are no or few indications of harm from defibulation, reconstruction may lead to a worsening in sexuality‐related outcomes for as many as one in five women. Results from another systematic review document that most women appear to be satisfied with defibulation and reconstruction . Still, women's experiences with reparative surgeries are mixed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, although there are no or few indications of harm from defibulation, reconstruction may lead to a worsening in sexuality‐related outcomes for as many as one in five women. Results from another systematic review document that most women appear to be satisfied with defibulation and reconstruction . Still, women's experiences with reparative surgeries are mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that there may be obstetric advantages of defibulation over no defibulation, but there is a scarcity of research on other outcomes. This is paradoxical, given that sexuality‐related concerns and voiding and menstruation difficulties are the most common reasons for women seeking defibulation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that FGC in traditional contexts is considered to enhance femininity, one can draw the conclusion that the dominant discourse in anti-FGM campaigning contributes considerably to the growing demand for reconstructive clitoral surgery [ 35 ••]. In a review of outcomes after surgical interventions after FGC, the authors found differences in motivations for clitoral reconstruction: “some indication that specified reasons among women residing in Western countries and those in African countries are distinctive, with women in the West more often stating restoration of identity and aesthetic improvement as motivations” [ 67 , p. 985]. Yet, it can be noted that many women who have gone through the surgery report that they benefitted from it [ 64 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This paper explores women's reasons for seeking CR surgery as well as what they anticipate the surgery to accomplish, from the perspective of FGC-affected women in Sweden. The underlying study was inspired by, but did not seek to replicate, existing studies on CR, particularly regarding the reasons for requesting surgery (Berg et al 2017;Fold es, Cuzin, and Andro 2012), and the methodology (Andro et al 2009;Villani 2017).…”
Section: Introductionmentioning
confidence: 99%